Wokół kryzysu w myśleniu o dydaktyce normatywnej - Sarnecki, Robert; Porzucek-Miśkiewicz, Maria (Kultura-Społeczeństwo-Edukacja, 2018)
The learning process is subject to change. The direction of changes is not unambiguous and results from different paradigms. Didactics must be subject to changes resulting from psychological processes. They take into account the universal regularities of thinking, memory, perception, emotions and motivation. Learning and teaching are complicated process that should not take into account only one paradigm.